The impact of leader mindfulness in communication on employees' psychological safety - Sijin Du; Sijin Du; Sijin Du; Wenli Xie; Wenli Xie (Frontiers in Psychology)
IntroductionThis study investigated the mediating role of Leader Empathy and Interpersonal Trust between Leader Mindfulness in Communication and Employees' Psychological Safety. In addition, it also examined the positive moderating effect of employee mindfulness on multiple variables.MethodThe data collection for the study was conducted in two stages, with an interval of 4 months. The data collection method is to conduct a questionnaire survey on 506 employees. The data analysis phase was conducted using Amos and SPSS statistical software.ResultsThe results indicate that the leader mindfulness in communication has a positive impact on employees' psychological safety. Leader empathy and interpersonal trust play a mediating role between the leader mindfulness in communication and employees' psychological safety. Employee mindfulness plays a positive moderating role among multiple variables.DiscussionEmployees exhibit a very open and welcoming attitude toward the form of leader mindfulness in communication. Leaders can significantly alleviate the stress and psychological issues faced by employees through this approach. Practical strategies include promoting mindfulness training and requiring leaders to adopt leader mindfulness in communication. The study provides feasible suggestions to alleviate employees' psychological problems, enhance employees' psychological safety, create a harmonious and stable working environment, and improve organizational efficiency.